Long-Term Observation and Treatment of Epithelioid Haemangioendothelioma of the Mediastinum: A Case Report - Zhi, Qiuli; Ma, Zhoupeng; Lin, Guansheng; Pan, Jiangfeng; Chen, Bingye (Frontiers in Surgery, 2021)
Epithelioid haemangioendothelioma is a rare angiogenic tumour originating from vascular endothelial or pre-endothelial cells, and it can occur anywhere in the body, such as the liver, lung, bone, spleen, lymph nodes, parotid gland, and thyroid. In the fifth revision of the WHO classification, epithelioid haemangioendothelioma (EHE) was described as a malignant vascular neoplasm composed of epithelioid endothelial cells, distinct from epithelioid angiosarcoma. We, herein, report one patient with EHE of the left upper mediastinum who underwent resection and radiotherapy during the first therapeutic process. Multiple metastases occurred in the thoracic vertebrae 6 years later, and resection and multiple radiotherapies were performed. The condition of the patient remained stable at the last review in October 2020, and it has been more than 8 years since her first admission. The reasonable “take-away” lessons from the case are active treatment and prolonged surveillance.